Securing audio chat with cryptool-based twofish algorithm - Nurdin, Alya Aulia; Djuniadi, Djuniadi (Journal of Soft Computing Exploration, 2022)
Technology and the internet are growing very rapidly in society making it easy for people to share information and communicate with each other. However, the security of such data or information is something that should be highlighted. The utilization of technology and the internet has many security gaps that can make data or information vulnerable to being stolen and even misused. Valuable data or information is very likely to be accessed by unauthorized people. On the other hand, data and information are prone to be illegally altered and even duplicated. In connection with various possible data or information security issues, it is necessary to do a data security. The purpose of this study is to secure audio chat using a Cryptool-based Twofish algorithm. Based on research conducted, the security process with encryption and decryption simulations was successfully carried out on audio chat. Audio chat sent via IP Address can be encrypted into ciphertext and can be decrypted back into audio at a speed of 15.78 kB/s and the resulting size is also still the same, which is 160 packets. This Twofish algorithm proved to be well usable because the size and quality of chat audio generated from decryption is still the same as audio chat before it is encrypted.